Forage production and nutritive value of maize hybrids and local oats in Costa Rica - Sánchez-Ledezma, William (2018)
In the area, there are no selected maize materials for forage production, tall and long-cycle creole maize varieties are used, there are overturning problems that make management difficult. The study was conducted in the dairy highlands of Costa Rica at an altitude of 2200 m, between 2008 and 2009. This study was made in order to compare the forage production and the nutritive value of nine maize hybrids (Zea mays) with local oats (Avena sativa) in a randomized design of complete blocks and three replicates. Harvesting took place at grain stage called milky-doughy (4 and 6.5 months for oats and maize hybrids). Oats had a dry matter yield (14 t/ha) and dry matter digestibility (8.7 t/ha) higher (P<0.0001) than hybrids (7.8 and 4.9, respectively). Although hybrids showed a higher (p<0.05) percentage of dry matter (mean 19.2) and in vitro dry matter digestibility (mean 63.2), oats had percentages of 16.7 and 61.9 within the same order. The percentage of crude protein in oats (14.2) was higher (p <0.05) than maize hybrids (mean 10.9). The creole oat variety showed a higher forage resource than the evaluated hybrid maize.